ARTIFICIAL INTELLIGENCE IN EDUCATION, LAW AND SCHOOL MANAGEMENT IN PUBLIC SECONDARY SCHOOL IN IDEATO NORTH LOCAL GOVERNMENT AREA OF IMO STATE (UNIZIK Journal of Educational Management and Policy, 2025)
This study investigated Artificial Intelligence in Education, Law and Security Management in Public Secondary School in Ideato Local Government Area of Imo State, Nigeria. The study adopted descriptive survey research design and was guided by two research questions. A random sampling technique was used to select 144 teachers drawn from the entire population of (228 teachers) in Ideato North Education Zone of the state. A four point scale questionnaire titled “|Artificial Intelligence in Education, Law and Security Management (ATELSM)” structured by the researcher, validated by experts was used for data collection. A reliability index of 0.82 using cronbach alpha was determined for the instrument and was adjudged to be reliable and adequate for the study. Data was analyzed using mean ratings. The findings among others revealed that, Artificial Intelligence Tools were not available for teachers and students to teach and learn through electronics learning. The findings also revealed that teachers and students experience some challenges for using Artificial Intelligence to teach and learn effectively through electronics media. Based on the findings, the researcher recommended that available Artificial Intelligence tools should be provided to the government to schools for effective teaching and learning in the schools through electronic devices. The researcher also recommended that seminars and conferences should be organized in the schools to guide the teachers on how to use Artificial Intelligence effectively.
Keywords: Artificial Intelligence, Education, Law, School Management.